Investment funds – returns, risk and fees dependencies in Poland and UK in 2015 - Fraś, Alicja (Research Papers of Wrocław University of Economics, 2018)
Common phenomenon is the positive relation between risk level and return. Investor would also expect that the higher the mutual fund fee, the more active is the management, so risk is increased. Then, as a payoff for higher charges and risk, he or she anticipates higher returns. It turns out that at least in Poland in 2015 rates of return did not go up as risk increased, and most risky funds lagged by 5 pp. in rates of return. Most expensive funds in Poland lost 8 pp. versus the cheapest, whereas in UK top-fees funds’ returns were 2 pp. lower
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 519, s. 63-76
Keywords: correlation; investment funds; fees; rate of return; korelacja; fundusze inwestycyjne; opłaty; stopa zwrotu